UX gardens. Issue 1 (4th February 2014) - Fox, Robert
Abstract : Purpose: – This column aims to explore the important role of user experience analysis in the design of web based digital library services and tools. Design/methodology/approach: – Three key areas of UX are talked about. Findings: – Three key areas of UX are applied to digital librarianship. Originality/value: – The needs of the patron populations served by individual libraries are unique, but certain design principles can be followed that will significantly enhance the user experience. This column contributes to the discussion regarding those principles.